Do students with different cognitive styles have similar levels of statistical thinking? - Siti Lailiyah; Nuriyatul Muslimah; Sutini Sutini (Universitas Islam Negeri (UIN) Mataram, 2021)
[English]: This study aims to examine and compare students’ level of statistical thinking with different cognitive styles (Field-dependent, FD and Field-independent, FI) in solving mathematical problems. It is descriptive qualitative research involving 31 ninth-graders given the Group Embedded Figure Test (GEFT) to determine their cognitive styles. From the results of GEFT, four students with two cognitive styles and high mathematics ability were selected as participants. A test and interviews were administered for data collection. The test was analyzed based on the level of statistical thinking indicators, and the interview results were used to confirm and explore the students' statistical thinking. The results of data analysis revealed that in representing data, both FI and FD students are at transitional level. In other stages of statistical thinking: describing data display, organizing and reducing data, analyzing and interpreting data, FD students reach a quantitative level meanwhile FI students are at an analytical level. Indeed, students with FI cognitive style have a higher level of statistical thinking than FD students. This finding shows that characteristics of students with FI, for example, being more analytic, support the achievement of better levels of statistical thinking. [Bahasa]: Penelitian ini bertujuan untuk mengidentifikasi dan membandingkan level berpikir statistik siswa dengan gaya kognitif berbeda (Field-dependent, FD dan Field-independent, FI) dalam memecahkan masalah matematika. Penelitian ini merupakan penelitian kualitatif deskriptif yang melibatkan 31 siswa kelas 9. Siswa tersebut diberikan Group Embedded Figure Test (GEFT) untuk menentukan gaya kognitif. Selanjutnya, dipilih 4 siswa pada kedua gaya kognitif dengan kemampuan matematika tinggi. Data dikumpulkan melalui tes dan wawancara. Hasil tes dianalisis berdasarkan indikator level berpikir statistik dan hasil wawancara dianalisis untuk mengonfirmasi dan menggali lebih dalam berpikir statistik siswa. Hasil analisis data menunjukkan bahwa dalam menyajikan data, siswa FD dan FI berada pada level transisional. Pada tiga tahap berpikir statistik lain; menjelaskan sajian data, mengatur dan mengurangi data, menganalisis dan menerjemahkan data, siswa FD berada pada level kuantitatif sedangkan siswa FI berada pada level analitik. Dalam hal ini, siswa dengan gaya kognitif FI memiliki level berpikir statistik yang lebih tinggi dibandingkan dengan siswa FD. Hasil penelitian ini menunjukkan bahwa karakteristik siswa dengan gaya kognitif FI, misalnya cenderung lebih analitis dibandingkan FD, mendukung capaian level berpikir statistik yang lebih baik.